ORGANIZING THE TRAINING PLAN OF WEEKLY MICROCYCLES OF YOUNG ATHLETES ENGAGED IN FREEDOM WRESTLING - Sultonov Shukhrat Nurmakhamatovich (Galaxy International Interdisciplinary Research Journal, 2023)
In this article, the method of effective organization of training plan in weekly microcycles of 14-15-year-old freestyle wrestlers training in the primary training group is developed.